Pengaruh Penggunaan Podcast Mendoan Terhadap Pembentukan Perilaku Wajar Mengumpat Generasi Z di Kota Malang - Clara Aprilia Gozali (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Mass media and social media have transformed patterns of communication and behavior, especially among Generation Z. Amidst a variety of podcasts that use Indonesian language as their communication medium, podcast Mendoan chooses to disregard the norms of polite and proper language usage as an example for its listeners. This study aims to investigate whether the use of podcast Mendoan influences the normalization of swearing behavior among Generation Z in Malang City. The researcher employs cultivation theory, which emphasizes the influence of mass media on shaping perceptions and beliefs. This research utilizes a quantitative approach to test hypotheses with a sample size of 100. The findings indicate that the use of Podcast Mendoan in shaping the normalization of swearing behavior among Generation Z in Malang City demonstrates the influence of new media. Referring to the media's influence on shaping perceptions, understanding, and individual behaviors towards social reality, podcast Mendoan may lead its listeners to view swearing behavior as something commonplace or acceptable in daily conversations.